Optimizing School Library Strategies to Strengthen Reading Literacy Among Elementary Students: A Qualitative Case Study - Ayu Novita; Fitri Puji Rahmawati (Universitas Ahmad Dahlan, 2026)
Reading literacy is an important foundation for students’ learning and academic development in elementary education. However, literacy achievement among elementary school students in Indonesia remains relatively low. This study aimed to examine school library strategies used to strengthen reading literacy among students at Mojosongo V Public Elementary School, Surakarta, Indonesia. This study employed a qualitative case study design involving librarians, teachers, and students. Data were collected through semi-structured interviews, participatory observations, and document analysis. The data were analysed using data reduction, data display, and conclusion drawing, while validity was ensured through source triangulation and member checking. The findings showed that reading literacy was supported through strengthening library management, implementing literacy programs through the School Literacy Program, encouraging teacher and parent involvement, improving access to reading facilities, and providing reading materials relevant to students’ interests. Several challenges were also identified, including limited human resources, inadequate digital infrastructure, and limited updated book collections. In addition, students showed higher reading motivation through literacy reward programs and regular literacy activities integrated into school routines.